PENINGKATAN PENGELUARAN ASI DENGAN KOMBINASI PIJAT OKSITOSIN DAN TEKNIK MARMET PADA IBU POST PARTUM (LITERATUR REVIEW) - Lieni Lestari; Melyana Nurul Widyawati; Admini Admini (JURNAL KEBIDANAN, 2018)
Breastmilk is very useful for babies at the beginning of their lives because it contains a lot of antibodies for the baby's immunity that can prevent diseases that cause the death of infants and toddlers. One of the factors that a mother cannot give immediate is breast milk expenditure that is not smooth in the first days after giving birth. The delayed release of breast milk can be caused by a lack of stimulation of the hormone oxytocin and prolactin which are very instrumental in smoothing out breastfeeding expenditure. This non effortless release of breast milk can be stimulated by a combination of Oxytocin Massage and Marmet Technique.               The aim of the study was to identify the literature review relating to oxytocin massage and marmet technique. Methods: This study uses literature (literature review) about the benefits of applying oxytocin massage and marmet techniques. The source for conducting this review is in the form of 8 research articles from 2013 to 2017. The research design was descriptive by analyzing two international journals and six national journals relating to oxytocin massage and marmet technique. Results: Oxytocin massage and marmet techniques can be categorized as safe and effective interventions to increase for the spending of breastmilk in postpartum mothers who experience problems with breast milk production. Conclusion: Oxytocin massage and marmet techniques can increase for the spending of breastmilk.